Joint estimation method of target number and orientation parameters for FDA-MIMO radar - Helin SUN; Hongyuan GAO; Yanan DU; Jianhua CHENG; Yapeng LIU (Tongxin xuebao)
To address the problem that the frequency diverse array MIMO (FDA-MIMO) radar requires a priori information on the target number when locating multiple targets and the multidimensional parameter estimation consumes a large amount of computation, a joint estimation method was proposed.The angle and distance dependence of the FDA-MIMO were utilized to transform the estimation of target number and orientation parameters into a multimodal optimization problem on the spatial spectrum, and a density-based multimodal differential evolution algorithm was designed to solve it, which reduced the computational load and did not require a separate target number estimation algorithm.Simulation results show that the proposed method outperformed the existing methods in estimating the target number and orientation parameters.It overcomes the application limitations of the existing orientation parameter estimation methods and can obtain optimal estimation results without quantization error.